Hb A1c versus 50 grams Glucose Screening Test for Screening Gestational Diabetes Mellitus - Kitiya Wutthibenjarassamee; Sukanya Srinil; Maleechat Sripipattanakul (The Royal Thai College of Obstetricians and Gynaecologists, 2014)
Objective :To evaluate utility of HbA1c as a screening method for gestational diabetes mellitus (GDM) in high risk pregnant women.Material and Method:This diagnostic study was conducted at Khon Kaen Hospital between July 2012 and May 2013. Two hundred pregnant women with high risk of GDM underwent a conventional 50g glucose screening test (GST) and Hb A1c measurement as a new screening method at first antenatal visit. A gold standard diagnosis of GDM was 100g oral glucose tolerance test (OGTT) based on The National Diabetes Data Group (NDDG) criteria was performed next week. The optimal cut off value for Hb A1c was analyzed by receiver operating characteristic (ROC) curve.Results :The area under ROC curve of HbA1c to detect GDM was 0.75 (95%CI 0.67-0.84). Sensitivity and specificity of Hb A1c for screening GDM at 4.9%, 5.0% and 5.1% were 89.8% and 24.5%, 87.8% and 33.1% and 85.7% and 42.4%, respectively. The negative predictive value increased as the cut off values increased and reached 88.1%, 89.3% and 90.1% at Hb A1c 4.9%, 5.0% and 5.1%, respectively. Sensitivity and specificity of 50g GST at 140 mg/dL was 81.6% and 22.5%, respectively.Conclusion : The appropriate HbA1c cut off value for screening GDM was 5.0%. The sensitivity was higher than 50g GST at 140 mg/dL and high negative predictive value.